hsCRP level and cognitive function in ischemic stroke patients: systematic review - ., Feliana; Pertiwi, Junita Maja; Mawuntu, Arthur Hendrik Philips (International Journal of Research in Medical Sciences, 2022)
Increased level of High sensitivity C-reactive protein (hsCRP) is associated with poor ischemic stroke functional outcomes according to several previous studies. However, there are no studies that specifically evaluate cognitive function. This systematic study aims to perform a narrative analysis of hsCRP levels with cognitive function in ischemic stroke patients. A systematic search of research articles was carried out on electronic databases using the PRISMA guidelines and on the bibliography on the references of the relevant articles. The electronic databases used are PubMed/Medline, Cochrane, Wiley Online Library, Scopus, Science Direct, and Google Scholar. The included study designs were cross-sectional, case-control, and prospective cohort studies. The risk of bias was analyzed by using ROBINS-1 and the quality of research by using GRADE. From eight studies, there were four studies that in addition to examining hsCRP also examined other inflammatory markers i.e.; fibrinogen (1 study) and homocysteine (3 studies). The risk of bias assessment tool for ROBINS-I indicated a high risk of outcome assessment blinding for eight studies. The quality of studies was assessed by GRADE showed low quality. Results indicated an association between elevated hsCRP and poor cognitive outcome in ischemic stroke patients. The hsCRP examination can be considered in ischemic stroke patients to predict cognitive function. However, as a routine examination, further studies are still needed.